2019
DOI: 10.1002/hyp.13676
|View full text |Cite
|
Sign up to set email alerts
|

Study of isotopic seasonality to assess the water source of proglacial stream in Chhota Shigri Glaciated Basin, Western Himalaya

Abstract: The impact of surface melt patterns and the Indian summer monsoon (ISM) is examined on the varying contributions of end member (snow, glacier ice, and rain) to proglacial streamflow during the ablation period (June-October) in the Chhota Shigri glaciated basin, Western Himalaya. Isotopic seasonality observed in the catchment precipitation was generally reflected in surface runoff (supraglacial melt and proglacial stream) and shows a shift in major water source during the melt season. Isotopically correlated (δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…The LMWL shows a substantial difference in slopes and intercepts (Figure 3a). However, their slopes and intercepts are close to the GMWL and LMWLs previously reported in the Himalayan region (Ali et al., 2020; Dar, Rai, & Kumar, 2022; Hill et al., 2020; Jeelani & Deshpande, 2017; Kumar et al., 2010, 2020; Pant et al., 2021), and the Tibetan Plateau (Tian et al., 2001). Based on the predicted GWRM isoscapes, we determined new basin‐wide meteoric water lines using least‐squares regression.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The LMWL shows a substantial difference in slopes and intercepts (Figure 3a). However, their slopes and intercepts are close to the GMWL and LMWLs previously reported in the Himalayan region (Ali et al., 2020; Dar, Rai, & Kumar, 2022; Hill et al., 2020; Jeelani & Deshpande, 2017; Kumar et al., 2010, 2020; Pant et al., 2021), and the Tibetan Plateau (Tian et al., 2001). Based on the predicted GWRM isoscapes, we determined new basin‐wide meteoric water lines using least‐squares regression.…”
Section: Resultssupporting
confidence: 85%
“…Further, the observation that groundwater has a lower slope in GRB and BRB (6.1 ± 0.1 and 5.3 ± 0.3) and intercept (−0.8 ± 1.0 and −9.7 ± 2.1) compared to LMWLs suggests that subsurface infiltration overwhelmingly occurred with significant evaporative loss. Previous local groundwater investigations in HRB supported our observation of extensive evaporative loss during subsurface infiltration (Dar, Rai, & Kumar, 2022;Kumar et al, 2020) and groundwater being enriched seasonally compared to rainfall (Dar, Rai, & Kumar, 2022).…”
Section: Isotopic Patterns Of Different Meteoric Sources Across Hrbssupporting
confidence: 87%
See 1 more Smart Citation
“…Chhota Shigri Glacier receives ~29% of annual P in summer (mostly as snowfalls on the glacier). However, summer monsoon snowfalls were found to reduce the melt on Chhota Shigri Glacier, but the snowfalls on the non-glacierized area (53% of total catchment at the discharge site) provide additional water at the discharge site and therefore makes the precipitation–discharge relationship quite complicated (Azam and others, 2019; Kumar and others, 2020).
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…These values are in concordance with those reported for other mountain glacial basins around the world, even though different moisture sources are registered. For instance, Kumar et al (2018) and Kumar et al (2020) reported mean values of −13.2 ± 1.4 for δ 18 O and of −76 ± 10 for δ 2 H for glacial basins of the Indian Himalayas. Meanwhile mean values of −14.2 ± 2.5 for δ 18 O and of −98 ± 20 for δ 2 H were registered for the Tibetan Plateau by Zhao et al (2018).…”
Section: Resultsmentioning
confidence: 99%